Primary Atopic Disorders: Expanding Field of Inborn Errors of Immunity - Güzin Özçifci; Sena Nur Arbağ; Yasemin Kendir-Demirkol; Joshua D Milner (Turkish Journal of Immunology)
Inborn errors of immunity cover a broad spectrum of diseases from immune deficiency syndromes to hyperinflammatory conditions. Primary atopic disorders are a recent member of this spectrum as a group that embracing monogenic immune deregulatory diseases causing allergic and atopic phenotypes. Liable genetic alterations lead to signaling pathways and cellular functioning changes, which skew to type-2 immune responses. Elucidation of these pathways and identifying these disorders have the utmost importance, since early identification of some of these disorders significantly changes the prognosis and targeted treatments offer improved outcomes. In this review, these broad-spectrum of diseases including recent findings were categorized and affected pathways and clinical phenotypes were explained.